UPAYA MENINGKATKAN HASIL BELAJAR KETERAMPILAN LEMPAR TANGKAP BOLA KECIL DENGAN MODIFIKASI PERMAINAN TRADISIOANAL BOI (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This research is a classroom action research that consists of two siklus.Hasil studies showthat the approach can improve mastery of playing small ball throwing catching on fifth gradestudents of SDN Pucangrejo. Based on the test sikuspertama average of 9 to 10 times and anincrease in the cycle to two 11sampai 12 times within 30 seconds, the results obtained showthat pendekatanbermain dapatditeriam more easily by students. Conclusions from thisresearch is the method of learning can play a positive influence on the development of learnersin mastering the techniques of throwing and catching motivate students in learning to follow,and can add insight to teachers in developing various learning models.